2007
DOI: 10.1021/ed084p547
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Student Achievement in General Chemistry Following Participation in an Online Preparatory Course. ChemPrep, a Voluntary, Self-Paced, Online Introduction to Chemistry

Abstract: ChemPrep was developed to be a stand-alone preparatory short-course to help students succeed in general chemistry. It is Web-based and delivered using the OWL system. Students reported that the ChemPrep materials (short information pages, parameterized questions with detailed feedback, tutorials, and answers to questions through the OWL message system) permitted them to work independently without the need for textbook or lecture. On average, students who completed ChemPrep had higher grades in the subsequent G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 3 publications
2
42
0
Order By: Relevance
“…As reported in the literature, effect sizes with absolute values of 0.2 are small, 0.5 indicates a moderate effect, and 0.8 is a large effect. On average the preparatory general chemistry group shows a 0.47 effect size indicating a moderately positive effect on their prior preparation for general chemistry [24,34]. Table 2 shows a closer examination of the two groups broken down by individual Math ACT scores as analyzed by the difference in their numerical average final course grades and the effect sizes.…”
Section: Es =mentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in the literature, effect sizes with absolute values of 0.2 are small, 0.5 indicates a moderate effect, and 0.8 is a large effect. On average the preparatory general chemistry group shows a 0.47 effect size indicating a moderately positive effect on their prior preparation for general chemistry [24,34]. Table 2 shows a closer examination of the two groups broken down by individual Math ACT scores as analyzed by the difference in their numerical average final course grades and the effect sizes.…”
Section: Es =mentioning
confidence: 99%
“…Because of the quantitative nature of general chemistry, it has been shown that math preparedness plays a large role in success in this course [14]. Strategies to determine which students may be mathematically underprepared for general chemistry have been based on high school GPA, standardized college admission tests such as ACT and SAT exams, and chemistry placement exams that are usually administered online [10,13,15,24]. In order to better understand our science student population's readiness for general chemistry, the Toledo placement exam, which is an American Chemical Society Exams Institute exam for placement of students into general chemistry, was administered to our General Chemistry I students in the first week of class during spring 2015 and fall 2016 semesters.…”
Section: Identifying Mathematically Underprepared Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the students enrolled in general chemistry have apprehension about the course and are unsure of their ability to succeed [2]. The intrinsic nature of the subject and the psychology of human learning have caused the perception that chemistry is a difficult subject [3].…”
Section: Introductionmentioning
confidence: 99%
“…7 Other efforts include online preparation programs, extended recitations, and peer led mentoring and study groups. [8][9] Additionally, active learning methods in lecture and interactive faculty result in increased student engagement in the learning process during these classes. 10 Consistent with the students' portrayal of this hardness in introductory STEM courses, there is a vast literature spanning several decades that documents difficulties in conceptual understanding in chemistry and physics from kindergarten through the college years.…”
Section: Why Do Students Leave Stem Disciplines During Their First Yementioning
confidence: 99%